Relatório de Estágio Profissional "A Gestão das Expectativas de um Professor Estagiário - Um Percurso Atribulado" - Ricardo José Pimentel Anes (2019)
The following document portrays the experience that I lived as an intern all along my internship. During this report I'm going to aproach the aspects by wich I was motivated until I came to this place, as the expectations that I brought to this experience. Furthermore I'll also talk about my personal frustrations and the bad times that I exprienced during this time. I'm sure that I'm going to revive all of my thoughts related to the pedagogical pratice, the mistakes that I made, the indecisions and refletions. I'm also going to do a balance with all that this experience teached me and the things that contributed for my personal and professional developement. At last, but not least, I'll talk about the conclusions obtained with the study that I made, named: "Student's opinion about the importance that physical education may have in their future."